Incidence, epidemiological characteristics and factors associated with COVID-19 pneumonia among inmates, Phetchabun Province, Thailand - Thammaros , Tassana (Disease Control Journal, 2023)
This study aimed to assess incidence, describe epidemiological characteristics, and identify factors associated with COVID-19 pneumonia among inmates in the prison in Phetchabun Province, Thailand (prison A). This was a retrospective cohort study. The population in this study were inmates in prison A who were COVID-19 patients during August 1st to October 31st, 2021. The data were gathered by reviewing medical record. The variables were age, sex, weight, height, underlying conditions, onset date, date of receiving antiviral medication, and chest x-ray results. The data were quantified as the frequency, percentage, mean, median, minimum, maximum, and standard deviation. Data were further analyzed using chi-square test, Fisher exact test, and binary logistic regression. A p-value less than 0.05 was a statistically significant. The findings revealed the incidence of COVID pneumonia was 17.6% (280/1590). Female: male ratio was 1: 69. The mean±SD of age was 34.8±10.3 years: minimum 18 years and maximum 81 years. Most of patients had weight less than 90 kg and normal body mass index. The multivariate analysis illustrated that male (adjusted odds ratio (AOR)=8.8, 95% confidence interval (95% CI)=3.2-24.1, p-value<0.001), age≥ 60 years old (AOR=4.4, 95% CI=2.3-8.3, p-value<0.001), and patients with tuberculosis (AOR=3.1, 95% CI=1.8-5.5, p value<0.001) showed the statistical significance. Even though, the number of COVID-19 patients was high, incidence and mortality were lower than prior studies. It might be the result of favipiravir treatment in all patients. Moreover, the average age of patient was quite young, and might be healthy. The effectiveness of favipiravir should study further.